PENGARUH KONDISI KEUANGAN TERHADAP PRAKTIK MANAJEMEN LABA - Citra Surya Kartika Ratri (Jurnal Penelitian Teori & Terapan Akuntansi (PETA), 2019)
Earnings management is a manager's choice to influence earnings number, both income-increasing and income-decreasing. The purpose of this study is the first to find out if the company's financial condition affect the accrual earnings management in non-financial companies Indonesia. Second, to determine whether the implementation of IFRS effect on accrual earnings management in non-financial companies Indonesia. This study uses multiple linear regression model to examine the variables that are expected to have an influence on accrual earnings management. The dependent variable in this study is accrual earnings management with conditional revenue model, the independent variables in this study is that the company’s financial condition and the implementation of IFRS, and then control variables in this study is size, leverage, and ROA. The sample in this study consisted of non-financial companies listed on the Indonesia Stock Exchange during 2009 to 2014. The sample selection is done by purposive judgment sampling method in order to get the results of 990 companies for six years. The test results with STATA 10.0 shows that partially the company's financial condition and size negative effect on earnings management, then implementation of IFRS and ROA positive effect on earnings management, while leverage has no effect on earnings management. Simultaneously, the company’s financial condition, the implementation of IFRS, leverage, size, and ROA effect on earnings management. Key words: Earnings management, conditional revenue model, company’s financial condition, implementation of IFRS, size, leverage, ROA.